2022
DOI: 10.1136/bcr-2021-247954
|View full text |Cite
|
Sign up to set email alerts
|

Eagle syndrome and carotid artery dissection: a rare skull base cause of stroke

Abstract: Eagle’s syndrome is a rare collection of symptoms that occur secondary to an elongated styloid process or calcified stylohyoid ligament irritating its surrounding structures. Classically, this presents as unilateral throat pain or rarely, as acute neurological symptoms secondary to compression of the internal carotid artery: so called ‘stylocarotid syndrome’. Significant neurological events in teenagers, secondary to Eagle syndrome have not been reported. We discuss the rare case of a teenage boy, diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…e demographic, clinical characteristics, treatment strategies, and follow-up of the patients are summarized in Table 1. [1,2,5,6,10,[14][15][16][18][19][20][21]23,24,27,30,31,37,38,[42][43][44][45][46][47][50][51][52]54,55,57] e mean age of the patients was 48.2 years (range 30-72). In an article, one patient was described as a "teenager" but was not used for statistical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…e demographic, clinical characteristics, treatment strategies, and follow-up of the patients are summarized in Table 1. [1,2,5,6,10,[14][15][16][18][19][20][21]23,24,27,30,31,37,38,[42][43][44][45][46][47][50][51][52]54,55,57] e mean age of the patients was 48.2 years (range 30-72). In an article, one patient was described as a "teenager" but was not used for statistical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…5,16 Dissection can occur in younger patients without other risk factors for dissection, as in our case. 3,32,33 Compression of the carotid vessels can also affect the sympathetic nerves that travel on those vessels, leading to symptoms of Horner's syndrome, which can improve following styloidectomy. 24,34 A review of the literature revealed 15 cases of ICA dissection due to Eagle syndrome, which were treated with styloidectomy (Table 1).…”
Section: Observationsmentioning
confidence: 99%
“…24,34 A review of the literature revealed 15 cases of ICA dissection due to Eagle syndrome, which were treated with styloidectomy (Table 1). 1,3,4,7,14,15,20,24,[32][33][34][35] The median age at presentation was 46 years (interquartile range 41-55 years), and 11 (73%) of 15 patients were male. Three cases noted possible triggers, two of which were related to neck motion, whereas the third case occurred in a patient with a recent tooth extraction with tonsillar swelling.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 34 cases reported in the literature since the millennium, only a single case of symptomatic SCS in a pediatric patient has been reported. 29…”
Section: Clinical Manifestationsmentioning
confidence: 99%